Reducing Health Services for Refugees Through Reforms to the Interim Federal Health Program - Andrew C. Stevenson (McMaster University Library Press, 2018)
Since 1957 the Interim Federal Health Program (IFHP) has provided temporary health care coverage to refugees and refugee claimants, but in 2012 the Conservative government reformed the IFHP, reducing, or eliminating access to health services for these groups. The government framed the changes around fairness and safety, stating that it would save tax payers $100 million over five years, reduce incentive for migrants with unfounded refugee claims from coming to Canada, protect public health and safety, and defend the integrity of the immigration system. With a Conservative majority, the reform was easily implemented despite a lack of evidence supporting these claims. In 2014, the Federal Court rejected the government's notion of fairness and safety, ruling that the cuts were cruel and unusual treatment of an already vulnerable population. The government appealed this ruling but, in 2016, the Liberals took power and restored funding to the IFHP to pre-2012 levels. Ad hoc evaluations predicted inequitable and adverse impacts on refugees, negative impacts on health, and increased costs to refugees, provincial governments, and health providers. Overall the threats and weaknesses of this reform clearly outweighed the few and unconvincing opportunities and strengths of the program, leading to its demise.